Gedung Parlemen Australia dari Sudut Pandang Konsep Perancangan - Prawata, Albertus (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This paper explores the design concept of the Australian Parliament House in Canberra, Australia, which is achieved by international design competition won by Romaldo Giurgola. As a foreigner, his achievement winning the international competition for the new Australian Parliament House was remarkable. He was successfully applied the historic and symbolic values from the early Canberra master plan by Walter and Marion Griffin into his work, and he was also influenced by other architect’s works such as Louis Khan.